The Effect of Helicopter Parenting on Self-Differentiation Among Indonesian Emerging Adults: A Cross-Sectional Study Based on Bowen Family Systems Theory - Claudia, Christina; Bolang, Caroline Mathilda V.; Isaputra, Samuel A.; Sutanto, Sandra H. (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2025)
Emerging adulthood is a critical developmental stage marked by increasing independence and evolving family dynamics. A key challenge in family counseling in this transitional period is facilitating the balance between parental support and the development of self-sufficiency. This quantiative study examines the relationship between Helicopter Parenting (HP) and Differentiation of Self (DoS) among Indonesian emerging adults and its implications towards family counseling, using Bowen Family Systems Theory as a framework. A cross-sectional design was employed, with data collected from 215 Indonesian participants aged 18-30. Participants completed measures of perceived HP and DoS, and results were analyzed using correlation and regression analyses. Findings show a negative effect of HP on overall DoS, particularly in emotional distancing and relational sensitivity. These results support the notion that overparenting may hinder the individuation of emerging adults, reinforcing emotional reactivity and relational dependence, indicating a family projection process. The importance of understanding the effects of HP and the family projection process on the well-being of the family and future research directions are discussed.